Peran Lembaga Kepolisian dalam Perspektif Fiqh Siyasah - Diah Sari Pangestuti (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
Looking at the crime statistic, it shows the continuous increase of crime either in number and quality. Even more varied and creative. Therefore, in order to produce internal security and to maintain the wellbeing of the people, a special institution is needed to handle it, namely the Police Agency. By using normative legal research and combining it with an analytical approach in order to analyze the data descriptively and inductively, this study tries to determine the role of the Police agency based on Fiqh Siyasah. It is concluded that: firstly, in Indonesian, there is a Police Agency that is a state instrument that plays a role in maintaining public order and security, enforcing the law, providing protection and services to the public. Secondly, in Islamic Law, there is the Muhtasib Institution, which has a supervisory and controlling body. Thirdly, that the Police in Islamic and Indonesian Law has almost the same duties that are as law enforcement to maintain security and public order. However, because of the law in Islam covers both mu'amalah and 'ubudiyyah aspects, so the scope of police responsibility in Islam is broader.